The Progressive: a cross-linguistic study of English and Albanian - Kelmendi, Libron; Rexhepi, Sadije (Respectus Philologicus, 2025)
This study explores the use and distribution of progressive forms in English and Albanian. The English-Albanian analysis is significant as it examines how two linguistic systems organize and encode the progressive aspect, revealing the structural contrasts that define their grammatical frameworks. The theoretical part outlines English and Albanian progressive forms. The research analyses English progressive forms translated into Albanian and Albanian progressive forms translated into English. The paper focuses on the progressive be+verb-ing of English. Research shows that, of the two Albanian progressive forms, the po participle (despite being limited to the present and imperfect) is more common and frequently used than the jam+duke+participle structure. There is a difference in how progressive forms are translated between English and Albanian. While 50% of Albanian po forms correspond to English progressives, 58% of English progressives are translated into Albanian using po, reflecting a nuanced difference in their usage across the languages. In conclusion, this shows that the status of the English progressive aspect differs from that of the Albanian progressive.
Keywords: English language; Albanian language; aspect; progressive aspect; progressive forms